Humedal para la disminución de la contaminación por los residuales líquidos de Ronera Central - Gutiérrez López, Leidy María; Suárez González, Maylín (My University, 2017)
El trabajo se realizó en La Ronera Central “Agustín Rodríguez Mena”. Se hace una valoración de las normas de vertimiento de los residuales líquidos, para introducir el uso de tecnologías más eficientes y compatibles con el medio ambiente. Teniendo en cuenta lo anterior, se propone la presente investigación que tiene como objetivo general: La propuesta de la construcción de un Humedal de flujo subsuperficial para el tratamiento de las aguas residuales vertidas a la Laguna de Oxidación que permita mitigar los daños provocados al ecosistema. El trabajo se estructuró en 2 capítulos; el marco teórico, las características generales y específicas en materia de contaminación por residuales líquidos y la aplicación de técnicas de análisis a la realidad empresarial. Para el cumplimiento de este objetivo se realizó una amplia búsqueda bibliográfica y finalmente se arriban a conclusiones derivadas de la investigación realizada.

he investment process in Cuba envisages a project aimed at alleviating the effects of the intense drought that the country has suffered in recent years, taking into account the potential here to make sea water fit for human, domestic and industrial consumption.This is part of a program aimed at ensuring the supply of water in those areas where it is complex to get through conductors, or it is very expensive to supply the vital liquid by conventional means. Taking into account the above, it is necessary to know the cost of this technology, for which the present research is proposed, whose general objective is: To expose the considerations calculating costs for seawater desalination plants by reverse osmosis. In the paper we consider the factors that affect the cost of m3 desalinated water by Reverse Osmosis in the country, considering that this technology is considered the most efficient based on its best water pressure, the feasible expansion of the Plants and their great reliability. In order to fulfill this objective, an extensive bibliographical search was made and finally conclusions are arrived at based on the research carried out.
Wetland for the reduction of contamination by liquid residuals from the Central Rum Factory
Keywords: Humedal; Planta Desalinizadora; Osmosis Inversa